2002
DOI: 10.1029/2001gl014441
|View full text |Cite
|
Sign up to set email alerts
|

Lithosphere and asthenosphere of the Tien Shan imaged by S receiver functions

Abstract: [1] The S receiver function technique was applied to the recordings from 36 broad-band stations in the Tien Shan. The results reveal a pronounced difference in the properties of the lithosphereasthenosphere of the Tien Shan and those of the neighboring platforms. Beneath the Tien Shan, an upper-mantle lid with an S velocity of about 4.5 km/s is underlain at a depth of about 90 km by a low-velocity zone, where the S velocity drops to 4.1 -4.2 km/ s. Trends of P and S travel time residuals are consistent with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 11 publications
(17 reference statements)
1
69
0
1
Order By: Relevance
“…Ambient noise tomography manifested low velocity within the mantle lid beneath the Tienshan orogenic belt (Li et al, 2012). Receiver function analyses showed a crustal thickness of ~60 km beneath the most parts of the Tienshan orogenic belt with variations of ~20 km under the adjacent platforms (Bump and Sheehan, 1998;Oreshin et al, 2002;Vinnik et al, 2004;Kumar et al, 2005). Tian et al (2010) suggested that the detached lithosphere may have descended to the bottom of the mantle transition zone and small-scale upwelling may have ascended from the lower mantle beneath the central Tienshan and adjacent regions.…”
Section: Introductionmentioning
confidence: 96%
“…Ambient noise tomography manifested low velocity within the mantle lid beneath the Tienshan orogenic belt (Li et al, 2012). Receiver function analyses showed a crustal thickness of ~60 km beneath the most parts of the Tienshan orogenic belt with variations of ~20 km under the adjacent platforms (Bump and Sheehan, 1998;Oreshin et al, 2002;Vinnik et al, 2004;Kumar et al, 2005). Tian et al (2010) suggested that the detached lithosphere may have descended to the bottom of the mantle transition zone and small-scale upwelling may have ascended from the lower mantle beneath the central Tienshan and adjacent regions.…”
Section: Introductionmentioning
confidence: 96%
“…Despite these complications, there has been renewed interest in recent years in teleseismic S-to-P conversions as means of characterizing the lithosphere to asthenosphere boundary (e.g., Kawakatsu et al, 2009;Kumar et al, 2005;Li et al, 2004;Oreshin et al, 2002;Rychert et al, 2007;Vinnik et al, 2005;Yuan et al, 2006). The growing waveform archive afforded by the profusion of modern digital networks has enabled stacking of large quantities of data to mitigate the low signal-to-noise ratios that characterize these phases, resulting in important new insights into this enigmatic structure (Eaton et al, 2009;Rychert et al, 2010).…”
Section: Geometrical Preliminariesmentioning
confidence: 98%
“…In a narrow corridor along the island chain, the LAB is observed to thin to $60 km at the northwest end of the chain. Oreshin et al (2002) found the LAB at 90 km depth beneath the Tian Shan from S receiver functions. Revenaugh and Jordan (1991b) found the LAB at 60 km depth from longperiod ScS reverberations in several regions of the western Pacific, but did not observe it in continental regions.…”
Section: The Gutenberg Discontinuitymentioning
confidence: 99%